The Influence Of Tiktok Beauty Reviewers Videos And Information Processing On Purchase Decisions Of Hanasui Lip Products In Malang City - Kirana, Elisya Anita; Ahya, Awaludin (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
Tiktok is one of the most popular social media platforms among many people. Beyond entertainment, it offers educational and beauty-related videos. The app presents a variety of videos, where the tiktok feed shows content that aligns with our preferences. Beauty review are individuals who frequently upload beauty content, such as product reviews and makeup tutorials that follow current trends.The purpose of this study is to determine whether beauty review content influences the information processing of purchasing decisions for Hanasui lip products. The respondents of this study are 100 female university students in Malang City who use Hanasui lip products more than twice. The method used this reaserch is quantitative meth population in this  study were early 18-25 years old student in Malang city The results show The results revealed that the combined influence of these factors on purchase decisions was 39.1%.The analysis showed that tiktok Beauty review (X1) had a significant impact on purchase decisions (Y), as indicated by a significance value of 0.000, which is less than 0.05. Similarly, information processing (X2) also exhibited a significant influence on purchase decisions (Y), with a significance value of 0.002, less than 0.05.This research provides new insights for beauty product consumers on how to leverage the tiktok platform and encourages consumers to be critical of information before making a purchase.